ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL PADA SAHAM JAKARTA ISLAMIC INDEX DENGAN MENGGUNAKAN SINGLE INDEX MODEL - Dwi Putri Puspita, - (2019)
This research is a type of descriptive research with a quantitative approach that aims to determine the formation of optimal portfolios using the Single Index Model. The sample used consisted of 18 companies out of a total population of 42 companies, namely companies that had appeared in the Jakarta Islamic Index (JII) list during the period June 2016 to May 2019. The results of analysis on historical closing prices during the 5 periods namely June 2016 to November 2016, December 2016 to May 2017, June 2017 to November 2017, December 2017 to May 2018, and June 2018 to November 2018 shows that the optimal portfolio is formed which consists of 5 shares, among others ADRO, INCO , PTBA, UNTR, and SMGR with proportions of 8,761%, 30,213%, 9,168%, 45,834% and 6,025% respectively.